Pengaruh Peristiwa Politik (Pemilu Presiden dan Pengumuman Susunan Kabinet) Terhadap Saham Sektor Industri Di Bursa Efek Indonesia - Siti Wardani Bakri Katti (CAPITAL: Jurnal Ekonomi dan Manajemen, 2018)
ABSTRACTPolitical events is one of the non-economic risks that may affect the investor's decision to invest in the capital market. The purpose of this article to determine the reaction and the difference of abnormal return of stock industry sector in Indonesia Stock Exchange (IDX) between before and after the political events (the presidential elections and the announcement of the cabinet line). Selection of industrial sector companies as research objects based on the premise that the industrial sector is the main sector driving stock trading in the IDX. This article using event study method to measure the market's reaction to events of national politics. In conducting this article used the data Composite Stock Price Index (JCI) as well as daily stock trading data on the industrial sector. Based on the results of the sample selection using purposive sampling, the sample in the study of 40 companies. The results can be concluded that there are abnormal returns around the national political events, but there are no differences in Average Abnormal Return (AAR) before and after the political events. This shows the predictions and information received by the stock market participants are relatively the same.Keywords: Political Events, Presidential Elections, Stock Market, Abnormal Return, Event Study